Model Manajemen Produksi Media Digital Berbasis Live Streaming Di Ceria Tv Pekanbaru - tambes, reski pulpi; Yasir, Yasir (Komunika : Jurnal Ilmiah Komunikasi, 2023)
Ceria Tv is one of the local television stations that broadcasts through Live Streaming channels in Pekanbaru City, Riau. Ceria Tv provides updated information and becomes a forum for communities in Pekanbaru, especially to channel talent and self-development through its programs. The purpose of this research is to find out how the Live Streaming production management model at Ceria TV, namely in the management of pre-production, production and post-production. This research is a qualitative research with descriptive qualitative method that uses management models. Informants in this study were determined purposively, which had been selected with certain considerations. Data collection techniques in this study include interviews, observation and documentation. The results of this study indicate that Ceria Tv uses two management models, namely the POAC model (Planning, Organizing, Actualling and Controlling) which is the model used for the Ceria Tv program itself while the PIE model (Planning, implementation and evaluation) is the model used to event in collaboration with Ceria Tv. In the pre-production stage of the Ceria Tv program planning which includes: Determination of Ideas, Program Objectives, Target Audience, Costs, Production Permits and Preparation, all of this is done by Ceria Tv itself. While the pre-production event planning: Determination of Idea, Location,Production Permit and Preparation is carried out by the event party. At the production stage of the Ceria Tv program, production supervision: Audio and Visual Readiness, Cameraman, Mixing, Live Editing and Live Streaming. At the production stage the event includes: Responsible for Lighting, Audio/sound, Lietrik, Stage Decoration, Live Editing and Live Streaming. In the post-production stage of the Ceria Tv program, namely: Finishing, Evaluation, Uploading, and Share Link (Promotion). In the post-production stage, the event includes: Finishing, Event Team Evaluation, Team Evaluation, File Sharing, and Uploading.